2016
DOI: 10.1039/c6nr05168e
|View full text |Cite
|
Sign up to set email alerts
|

Strongly polarized quantum-dot-like light emitters embedded in GaAs/GaNAs core/shell nanowires

Abstract: Recent developments in fabrication techniques and extensive investigations of the physical properties of III-V semiconductor nanowires (NWs), such as GaAs NWs, have demonstrated their potential for a multitude of advanced electronic and photonics applications. Alloying of GaAs with nitrogen can further enhance the performance and extend the device functionality via intentional defects and heterostructure engineering in GaNAs and GaAs/GaNAs coaxial NWs. In this work, it is shown that incorporation of nitrogen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 67 publications
3
31
1
Order By: Relevance
“…They predominantly crystalized in the zinc-blende crystal structure and had only few structural defects (below 5 twins per micrometer) within the bottom part of the wire of 1-2 m, though the twin density progressively increased towards the NW top [45].…”
Section: Methodsmentioning
confidence: 99%
“…They predominantly crystalized in the zinc-blende crystal structure and had only few structural defects (below 5 twins per micrometer) within the bottom part of the wire of 1-2 m, though the twin density progressively increased towards the NW top [45].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to a broad background emission that stems [30] from radiative recombination of excitons weakly localized within long-range potential fluctuations in the Ga(N, As) shell, the spectra contain numerous sharp PL lines. We have previously shown that these lines originate from strongly-localized QD-like emitters within the Ga(N, As) shell with the principal quantization axis of the QDs preferentially aligned along the NW growth axis (z) [20]. The weak emission observed at energies exceeding the Ga(N, As) band gap (approximately 1.4 eV for [N] = 0.5%) stems from the GaAs core [32] and will not be discussed further in this paper.…”
Section: Polarization-resolved Spectroscopymentioning
confidence: 99%
“…Recently, we have shown that the spontaneous QD formation is facilitated in NW heterostructures based on dilute nitride alloys, such as GaAs/Ga(N, As) core/shell NWs [20]. Here, the QDs are formed in the active Ga(N, As) shell due to short-range fluctuations in the N composition that enable carrier confinement due to the giant band gap bowing [21]: incorporation of only 1% of nitrogen in GaAs reduces the band gap energy by approximately 0.14 eV.…”
Section: Introductionmentioning
confidence: 99%
“…19 The numerous fine features overlapping with the broad peak could be attributed to excitons strongly confined in quantum-dot like states induced by short-range fluctuations in the nitrogen composition which are superimposed on long-range alloy disorder. 27 The third peak at around 0.93 eV may be caused by N related defects, which is often seen in dilute nitride materials. 22,28 The N composition is estimated to be $0.8% using the band anti-crossing (BAC) model and PLE spectra detected from GaAs/GaNAs core-shell NWs in Fig.…”
mentioning
confidence: 99%